John Lennon žije a vzkazuje… - Cílek, Václav (Lidé města, 2006)
Fortunately, graffiti has its own quite unclear terminology. Originally, tag was a symbol of an American street gang and it delimited its territory. Symbols must be clearly visible, wide and drawn in self-confident strokes. Street walkers, i.e., practical social street workers can understand tags and they know that if a tag of next door clan appears in a foreign territory, a war is declared. American street gangs often serve a criminal function - they control drug trade, and they also keep certain order. When you move into a poor neighborhood you might be visited by gang members offering protection of your apartment against thieves for a certain payment. This is more reliable than an insurance institution. In a given territory, they have a monopoly on crime and they push out other criminals. In this case, tag is a clear indication who should be paid. Majority of European tags has a different origin. It is just a signature. They are created primarily by youths between 14-17 years old - sometime between the 8th grade and vocational school. I know them to certain extent since my wife works as in primary school teacher in a housing development. These are quite nice boys coming from somehow broken homes. One can talk to them. They have experienced nothing good in their lives and feel their future does not hold anything bright, either. To make a tag in a visible place or even better in a train passing through the world is one of few possibilities to draw attention to oneself. At the same time, to create a tag or more complex creation in a dangerous place, such as a smokestack or roof over a police station, is a brave act connected with coming -of-age ritual. Probably just like a Masai boy killing a lion. I did it therefore I am a man! Only immature character must prove such an adventure over and over again. Others in our society full of insecurities and worries just calm themselves by spraying a building and do not think about it one bit. They are able to spray even where it is prohibited – on rocks or in caves. For number of years now, spelaeologist hide their underground structures to prevent some brain-fried space cadet who hasn’t got a clue to damage them.